MODL-34. DECELLULARIZATION OF HUMAN AUTOPSY BRAIN TISSUE TO GENERATE A 3D EXTRACELLULAR MATRIX FOR MEDULLOBLASTOMA AND ATYPICAL TERATOID/RHABDOID TUMOUR MODELLING. (14th November 2022) - McCrorie, Phoebe; Porter, Harry; Vinohar, Jeffy; Diksin, Mohammed; Scurr, David; Rahman, Ruman
Abstract: INTRODUCTION: Childhood medulloblastoma (MB) and atypical teratoid/rhabdoid tumours (AT/RT) are malignant brain tumours occurring in the posterior fossa, for which prognoses remains particularly poor for the MB Group 3 subtype characterised by amplification of the Myc oncogene and for AT/RT in general. Current in vitro models for these neoplasms rely on non-coated plastic, various hydrogels, or animal-derived extracellular matrix (ECM), which fail to recapitulate the physiological environment from which the cells are derived from. METHODS: We have developed a method to decellularize ex vivo human brain tissue from different anatomical locations for the use in 3D in vitro models. Human cerebellar brain tissue was harvested from autopsy brain and sectioned into small cubes before bathing in a sodium dodecyl sulfate/phosphate-buffered saline mixture for several days, before washing and lyophilising. RESULTS: The optimised method for generation of decellularized human brain ECM successfully removes nuclei as confirmed by histological staining and DNA quantification (DNA reduction of ≥ 60%). Orbitrap-Secondary Ion Mass Spectrometry analysis confirmed the retention of the ECM components laminin (C9 H11 N3 O2 Na + ), fibronectin (C9 H14 N4 O2 Na + and C20 H33 N7 O5 Na + ) and collagen (C4 H5 N2 O2 + ), with a reduction in cell membrane lipid components (glycerophosphocholine, C9 H19 NPO4 + ; phosphocholine, C5 H15 NPO4 + ; and choline, C5H14NO+) relative to control tissue, with a < 2 ppm accuracy, which was further corroborated by glycosaminoglycan and collagen assays. Multiple molecular subtype-specific AT/RT and MB cell lines have been successfully grown on decellularized cerebellar-ECM/PEGDA hydrogel, showing no reduction in metabolic viability using PrestoBlue and Cell Titer Glo assays. CONCLUSIONS: This methodology offers an innovative human-only high-throughput 3D drug screening model, whereby patient-derived MB or AT/RT cells are co-cultured with healthy human cerebellar astrocytes upon decellularized cerebellar ECM, which we term 'Tumoursphere Matrices'.